P149 Novel capillary blood point-of-care test for adalimumab and infliximab trough levels: Effects of abnormal blood conditions on the test result. (30th January 2023) - Brosi, L; Reinhard, C; Anchling, L; Afonso, J; Schuster, T; Gerhold, C B; Ricken, B
Abstract: Background: Patients suffering from inflammatory bowel disease can be treated with the biologics adalimumab (ADL) or infliximab (IFX). Previous studies demonstrated the usefulness of therapeutic drug monitoring (TDM) to adjust the patient's biologic concentration individually. Commercially available rapid assays support laboratories in the fast and easy detection of ADL and IFX concentrations but the assays' dependency on serum as analyte matrix is a general hindrance for TDM, as serum preparation from whole blood is time-consuming and requires laboratory equipment. Patients and clinicians would thus benefit from rapid point-of-care (POC) and easy to use assays that are independent of laboratory equipment. The objective of this project was to expand existing serum lateral flow assays for the analysis of ADL or IFX in capillary blood and investigate potential interactions resulting from the blood matrix. Methods: ADL and IFX lateral flow serum kits were optimized in such a way that both, capillary blood and EDTA whole blood can be used as analyte matrix by using disposable capillaries for blood collection and for its transfer into dropper bottles that are prefilled with chase buffer. To measure ADL or IFX levels with a POC lateral flow test cassette reader (BÜHLMANN Quantum Blue ® Reader) the mixture is then applied on an ADL or IFX lateral flow test cassette. Matrix agreement studies were performed to compare spiked EDTA whole blood and capillary blood samples with serum as reference. Additionally, spiked EDTA whole blood samples were treated to obtain three abnormal blood conditions: Icteric, hemolytic and lipemic blood. Bias in results exceeding 30% relative difference to the untreated sample was considered as an interference. Results: Spiked blood samples showed good agreement with reference serum samples. A bias of less than 15% at the clinical decision points for ADL (5 µg/mL and 12 µg/mL) and IFX (3 µg/mL and 7 µg/mL) was revealed. Observed relative differences between all tested abnormal blood conditions ranged between -20% and +26% for IFX and -16% and +5% for ADL. Conclusion: Two POC assays for the determination of ADL or IFX in capillary blood or EDTA whole blood samples were successfully developed and can be used by healthcare professionals with time to results of only 15 minutes and without the need for additional laboratory equipment. No systematic interferences were detected with treated EDTA whole blood samples, which could appear when using blood as analyte matrix. The excellent agreement to serum trough levels shows that the POC adalimumab/infliximab capillary blood assays are ideal for therapeutic drug monitoring analysis at a clinician's office or an infusion site.